How International law Work A Rational Choice Theory - Maulana, Mursal (Padjadjaran Journal of International Law, 2017)
BOOK RIVIEWTitle                    : How International law Work                             A Rational Choice TheoryAuthor                 : Andrew T GuzmanPublisher             : Oxford University Press Does international law affect state behavior?. Why would states pay any attention to international law in the absence of coercive enforcement mechanism?. What do we mean when we say international law is “binding”, given that states can almost always to violate it?. These intriguing and philosophical questions raised by the author to make sure that we had grasped at least one answer. If not, we were failed to understand the nature of international law. These question also remains us about traditional debate between proponent and opponent of international law such as Hobbes, Spinoza and Austin. But, in the 21st Century we are not debating or neglecting the existence of international law anymore.